2016
DOI: 10.1002/pon.4144
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapies for informal caregivers of patients with cancer and cancer survivors: a systematic review and meta‐analysis

Abstract: ObjectiveInformal caregivers (ICs) of patients with cancer and cancer survivors report a number of psychological and physical complaints because of the burden associated with providing care. Given the documented effect of Cognitive Behavioral Therapy (CBT) on ICs' common psychological complaints, such as anxiety and depression, the objective was to conduct a meta‐analysis on the effect of CBTs for adult ICs.MethodsA literature search was conducted in order to identify all intervention studies on adult ICs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 52 publications
3
51
0
Order By: Relevance
“…These changes were acceptable to caregivers. Although some studies fail to find efficacy for cognitive behavioral therapy interventions similar to PEPRR for cancer caregivers, the present study replicated efficacy in reducing CG‐distress across two different transplant programs (academic and community) as well as three interventionists but without an impact on patient's FACT‐BMT.…”
Section: Discussionsupporting
confidence: 50%
“…These changes were acceptable to caregivers. Although some studies fail to find efficacy for cognitive behavioral therapy interventions similar to PEPRR for cancer caregivers, the present study replicated efficacy in reducing CG‐distress across two different transplant programs (academic and community) as well as three interventionists but without an impact on patient's FACT‐BMT.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, we noted that use of additional mental health support services was significantly lower in the PEPRR group compared to TAU [35]. Some interventions using CBT strategies have failed to show significant effects on psychosocial outcomes [12]. The efficacy of PEPRR may be due, in part, to tailoring PEPRR to the specific needs of Allo-HSCT caregivers and integrating multidimensional intervention strategies, which may have addressed broader support needs.…”
Section: Discussionmentioning
confidence: 91%
“…A broad review of interventions for cancer caregivers across the illness trajectory that included all cancer diagnoses and varying caregiverpatient relationships showed benefits of psychoeducation, problem solving/skills building, and cognitive behavioral and interpersonal interventions [11]. A more recent systematic meta-analysis of cancer caregiver interventions by O'Toole and colleagues [12] reported that cognitive behavioral therapy (CBT) had negligible effect on caregiver outcomes, supporting the idea that interventions that integrate multiple evidencebased modalities may be more effective than traditional CBT interventions.…”
mentioning
confidence: 98%
“…was winsorized by replacing it with the lower or upper value of the range, thereby retaining the studies with an attenuated influence (cf Lipsey & Wilson, 2001;O'Toole, Zachariae, Renna, Mennin, & Applebaum, 2016)…”
mentioning
confidence: 99%